Capturing the City. (5th June 2019) - Peters, Robbie
Abstract: In this essay I use Surabaya as a case study to argue that today's data‐based urbanism excludes people from the city. Data‐based urbanism differs from the revolutionary and counterrevolutionary urbanisms of the past in Surabaya that included people: the revolutionary form enabled the low‐income majority of the kampung neighbourhoods to capture the 'city as a whole' through infrastructure, while the counterrevolutionary form enabled that majority to capture the city in parts through their kampungs. To make the aforementioned points I give the concept of heterotopia a Southern context that brings the low‐income majority to the foreground of urban studies.